The Influence of Employee Competence and Organizational Culture on Employee Performance with Work Motivation as Intervening at the Office of the Personnel and Human Resources Development Agency Binjai - Muhammad Fauzi; Muhammad Isa Indrawan (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This study aims to determine and analyze the Effect of Employee Competence and Organizational Culture on Employee Performance with Work Motivation as Intervening. This research method is a type of research using associative quantitative and this research was conducted at the Binjai Bkpsdm office. The research population used was 85 employees and used all populations to become a sample of 85 employees and used a saturated sample technique. Data collection used by distributing questionnaires and data sources used are primary data sources. The research model used is Path analysis and research measuring tools using Smart PLS version 3.3.3. The result of this research is that Organizational Culture has a positive and significant effect on employee performance. Organizational Culture has a positive and significant effect on Work Motivation. Employee Competence has no significant positive effect on Employee Performance. Employee competence has a positive and significant effect on work motivation. Work motivation has a positive and significant effect on employee performance. Work Motivation has a positive and significant effect on Employee Performance through Work Motivation. Employee Competence has a positive and insignificant effect on Employee Performance through Work Motivation.